Intensivist nurse: process of professional qualification - Isis da Silva Galindo; Silvana Silveira Kempfer; Priscila Juceli Romanoski; Daniele Delacanal Lazzari; Paula Bresolin; Pollyana Plautz Gorriz (Universidade Federal de Santa Maria, 2019)
Objective: to know the process of professional qualification of nurses to work in intensive care. Method: exploratory, descriptive and qualitative, performed with 20 nurses having their first professional experience in Intensive Care Unit (ICU), through a semi structured interview, from July to September of 2017. The results were analyzed from a content analysis perspective. Results: the results were grouped into two categories: the first addressed subjects related to the formative process of the intensivist that made them improve their knowledge and practice; the second deals with the formative decisions taken by nurses and their repercussions on their professional life. Final considerations: graduation is the construction of the nurse and the deepening of the knowledge for the intensivist performance and the attainment of success in this complex environment are believed in.